211k views
1 vote
What Is
-(v-1)=-6v+16​

2 Answers

3 votes

-(v-1)=-6v+16

We move all terms to the left:

-(v-1)-(-6v+16)=0

We get rid of parentheses

-v+6v+1-16=0

We add all the numbers together, and all the variables

5v-15=0

We move all terms containing v to the left, all other terms to the right

5v=15

v=15/5

v=3



User Jean Paul Galea
by
5.2k points
2 votes

Answer:


v = 3

Explanation:

-(v-1)=-6v+16

-v+1=-6v+16

grouping like terms

-v+6v=16-1

5v=15

dividing through by 5


(5v)/(5) = (15)/(5)


v = (15)/(5)


v = 3

User Roshnal
by
5.6k points